Socio-Technical Determinants of Electronic Medical Record Implementation Among Nurses: A Mixed-Methods Study in a Regional Indonesian Hospital - Hani Purwo Ariyanto; Yusuf Alam Romadhon; Aflit Nuryulia Praswati (Institut Kesehatan Suaka Insan, 2026)
Electronic Medical Records (EMR) aim to improve healthcare quality, but successful implementation relies on infrastructure, training, interoperability, and data privacy. This sequential explanatory mixed-methods study examines these factors' impact on hospital service quality at a regional Indonesian hospital. Quantitative data from 227 nurses, analyzed via multiple linear regression, were contextualized through qualitative stakeholder interviews. The results show all four factors significantly improve EMR service quality (R = 0.793), with infrastructure being the most dominant. However, qualitative findings highlight ongoing challenges: uneven infrastructure, limited continuous training, and inconsistent integration and security practices. Ultimately, maximizing EMR benefits requires a sustainable socio-technical approach integrating technological readiness, human capacity, and robust data governance.